2011
DOI: 10.1517/17425255.2011.575062
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic evaluation of decitabine for the treatment of leukemia

Abstract: Decitabine has established efficacy in MDS and shown promising activity in AML at low doses. Given decitabine’s favorable toxicity profile and emerging clinical efficacy, decitabine may be a low intensity therapeutic option for elderly patients with AML who are considered unfit for aggressive chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 81 publications
1
12
0
Order By: Relevance
“…The development of hypomethylating agents provides an alternative treatment strategy [1928]. This meta-analysis showed that decitabine brought considerable treatment response in elderly AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…The development of hypomethylating agents provides an alternative treatment strategy [1928]. This meta-analysis showed that decitabine brought considerable treatment response in elderly AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA methylation inhibitors, AZA and DAC, have been approved by the FDA for the treatment of MDS and AML (Jones & Taylor, 1980;Jones et al, 1982;Santi et al, 1984;Cheng et al, 2004;Bryan et al, 2011;Lübbert, 2000;Robak, 2011). As a side-effect, AZA and DAC can incorporate into the genome as part of its mechanism of action, which can cause mutations in the daughter cells if the cell does not die (Jones & Taylor, 1980;Santi et al, 1984;Davidson et al, 1992).…”
Section: Nucleosidic Dna Methylation Inhibitorsmentioning
confidence: 99%
“…It leads to DNMT depletion and genome hypomethylation. Toxic at high doses, decitabine is well tolerated at lower doses [132]. Recently, a study shows lower toxicity of a derivative of decitabine, the 2′-deoxy-5,6-dihydro-5-azacytidine at doses that induce similar DNA hypomethylation and gene reactivation [133].…”
Section: Current Drugs/dna Methylation Inhibitors and Clinical Trimentioning
confidence: 99%